DIVERSIFIKASI KREDIT TERHADAP PROFITABILITAS DAN PROBABILITAS KEGAGALAN BANK - Ari Christianti (Jurnal Keuangan dan Perbankan, 2011)
Loan diversification in the banking industry was an interesting topic to be studied. Unlike previous research,this study not only examined the effect of loan diversification on profitability but also on the probability ofdefault. Using panel data from banks listed on Indonesia Stock Exchange in 2004-2008 with FEM (fixed effectmodel) approach and weighting: cross section weight procedures, the results supported previous research thata high risk decreased the relationship between the diversification of loan and the profitability. However, therelationship between the diversification of loan and a probability of default decreased even when a high risk.The arguments for explaining this finding was that the probability of default was not an absolute measurementthat described an actual probability of default. In addition, this invention in banking practices related with thewrite-off action that could minimize the credit risk (NPL) so that the probability of default decreased especiallyfor private banks.